2015
DOI: 10.1177/1533317514568340
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Mental Health of Hispanic Dementia Caregivers in New York City

Abstract: Background Dementia prevalence and related caregiving burden are increasing, particularly among Hispanics. We studied the characteristics and mental health of Hispanic caregivers in New York City. Methods We recruited 139 Hispanic family caregivers. We collected data on socio-demographic characteristics and predictors of caregiver burden, measured with the Zarit Caregiver Burden Scale, and depressive symptoms, measured with the Geriatric Depression Scale. Results The mean age was 59.3 ± 10.4 years. The maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 53 publications
1
33
0
1
Order By: Relevance
“…Our recruitment strategy is based on previous experience49 and have been approved by the CUMC Institutional Review Board. Our target recruitment is 200 participants in 24 months or between 8 and 9 participants a month.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Our recruitment strategy is based on previous experience49 and have been approved by the CUMC Institutional Review Board. Our target recruitment is 200 participants in 24 months or between 8 and 9 participants a month.…”
Section: Methods and Analysismentioning
confidence: 99%
“…In Brazil, psychiatric hospital admission is recommended for severe cases when extra-hospital resources have been exhausted for the treatment or management of the problem, making it a moment of crisis for patients and of great impact to their families (19)(20)(21) . Indeed, other studies which reported only a mild burden of care, evaluated more clinically stable patients, at the time when the care was carried out at home or in outpatient care (22)(23) .…”
Section: Discussionmentioning
confidence: 99%
“…tarafından ruhsal hastalığı olan bireylere bakım verenlerle yapılan çalışma sonucunda bakım verenlerin orta-ağır düzeyde yük algıladığı belirlenmiştir. [42][43][44][45][46] Araştırmaların çoğunda bakımverenlerin yükünü etkileyen tanımlayıcı özelliklerin ve tanımlayıcı özellikler dışındaki değişkenlerin incelendiği görülmektedir. Ortaya pek çok sonuç çıkmasına karşın tanımlayıcı özelliklerin genel olarak, hastanın yaşı, cinsiyeti, tanısı, hastalık süresi ve evresi, tedavi alma durumu, bağımlılık düzeyi ve komorbid tanının varlığı, bakımverenin cinsiyeti, eğitim durumu, sosyoekonomik durumu, sosyal destek algısı, hastalıkla ilgili eğitim alma durumu ve ruhsal durumu olduğu belirlenmiştir.…”
Section: Discussionunclassified